2017
DOI: 10.1016/j.ridd.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of parent-reported quality of life of adolescents with cerebral palsy: A longitudinal study

Abstract: In general, impairment severity and socio-demographic factors were not predictors of lower adolescent QoL. However, pain, psychological problems and parenting stress were predictors of lower adolescent QoL in most domains. These are modifiable factors and addressing them may improve adolescent QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
36
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 29 publications
(41 reference statements)
10
36
4
Order By: Relevance
“…Investing in mother's education and provision of targeted interventions through mothers has the potential to increase understanding of effective mechanisms for improving the HRQoL of adolescent with CP. Moreover, the present study confirmed previous reports that caregiver mental health is an important predictor of adolescent HRQoL (9,35) although effect in the present study was small.…”
Section: Hierarchical Multiple Linear Regressionsupporting
confidence: 92%
“…Investing in mother's education and provision of targeted interventions through mothers has the potential to increase understanding of effective mechanisms for improving the HRQoL of adolescent with CP. Moreover, the present study confirmed previous reports that caregiver mental health is an important predictor of adolescent HRQoL (9,35) although effect in the present study was small.…”
Section: Hierarchical Multiple Linear Regressionsupporting
confidence: 92%
“…10,12 The concept of Oral Health-Related Quality of Life (OHRQoL) is related to the impact that health or oral diseases have on the functioning, well-being, or quality of daily life of the individual. 1 Few studies have evaluated possible factors associated with the HRQoL [13][14][15] and OHRQoL 3,16 of children with CP. The international literature reports the association of low HRQoL scores of children and adolescents with type of CP, 14 high levels in the evaluation of the Gross Motor Function Classification System, 13,14 low intellect, 14 pain, 15 epilepsy, 13 maternal psychological changes, 14,15 and parental stress levels.…”
Section: Introductionmentioning
confidence: 99%
“…1 Few studies have evaluated possible factors associated with the HRQoL [13][14][15] and OHRQoL 3,16 of children with CP. The international literature reports the association of low HRQoL scores of children and adolescents with type of CP, 14 high levels in the evaluation of the Gross Motor Function Classification System, 13,14 low intellect, 14 pain, 15 epilepsy, 13 maternal psychological changes, 14,15 and parental stress levels. 15 Regarding OHRQoL, the studies have shown their association with dental caries, 3,16 bruxism, 3 family income, 3,16 and communication skills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the majority of HRQoL research has been conducted in high-income countries (HICs) and findings suggest it is predicted by a range of personal and environmental factors (8). For example, a European study of 551 adolescents with CP found psychological problems and parenting stress predicted HRQoL whereas socio-demographic and impairment severity characteristics did not (9).…”
mentioning
confidence: 99%